The Role of Volleyball in a Guidance Program for Reducing Aggressive Behavior and Boosting Academic Achievement Among Students - Naji, Saif Alaa (STKIP PGRI SUMENEP, 2025)
Background:- This study explore the effectiveness of a volleyball-based guidance program in reducing?aggressive behavior and increasing academic achievement in students aged 12–13 years. Objectives Examine the relationship between aggressive behavior and academic achievement. Evaluate the effectiveness of a volleyball-based guidance program in mitigating aggression. Assess the program's impact on improving students' academic performance. Methods:- The approach was a descriptive and experimental study. whereas, the sample of students was randomly pared into an?experiment and control group, with no significant differences in aggressive behavior and academic performance . In the experimental group,?participants completed a volleyball-oriented guidance program for 6 weeks, which comprised 16 sessions. Aggressive?behavior was assessed with a validated 39-item questionnaire, and academic performance was assessed through school records. Data were analyzed?statistically with t-tests for pre- and post-test differences applied. Results:- A combined effect of the intervention was significant in reducing aggressive behavior in the experimental group (self-directed, other-directed and?property-directed) compared to the control group. Moreover, participation in the guidance program was associated with statistically significant improvements in academic achievement for the experimental group, further?indicating the effectiveness of the guidance program in promoting emotional regulation, cooperation, and attention. Conclusion:- Through this study, the students who followed the volleyball-based counseling?program showed decreased level of aggressiveness and improved their academic performance significantly. Applicable Remarks:- The current study highlights the potential of incorporating team sports such as volleyball into the school curriculum as a strategy to ameliorate behavioral problems for social and academic?benefit.